Промови Андрія Жука на засіданнях Загальної української ради (за матеріалами National Archives of Canada) - Магурчак, А.М. (Архіви України, 2012)
Публікуються промови члена Союзу визволення України Андрія Жука на засіданнях Загальної Української Ради в 1915–1916 рр., у яких аналізуються відносини СВУ з представниками Центральних держав для вирішення українського питання. Публикуются выступления члена Союза освобождения Украины Андрея Жука на заседаниях ЗУР в 1915–1916 гг., в которых дан анализ отношений СВУ с представителями Центральных государств для решения украинского вопроса. There are published the reports of Andriy Zhuk, the member of the Union of Liberation of Ukraine, represented on the meetings of General Ukrainian Rada during 1915–1916. It is also analysed the relationships of the Union of Liberation of Ukraine with the representatives of the Central States for the considering of the Ukrainian question.